If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 8 + -1f Solving 12 = 8 + -1f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add 'f' to each side of the equation. 12 + f = 8 + -1f + f Combine like terms: -1f + f = 0 12 + f = 8 + 0 12 + f = 8 Add '-12' to each side of the equation. 12 + -12 + f = 8 + -12 Combine like terms: 12 + -12 = 0 0 + f = 8 + -12 f = 8 + -12 Combine like terms: 8 + -12 = -4 f = -4 Simplifying f = -4
| 4x+5y-6x-y= | | .07x+x=5 | | X+2.6=58.4 | | 12.25xy= | | X+0.75=12.25 | | f(n)=5n+4n | | .2(b+10)-7=.3333333333333333333333333333333(b-9) | | 12.2=m+18.2 | | 10p^2-100p+20000=0 | | -6y-3=3y+15 | | .2(b+10)-7=.333333333333333333333(b-9) | | -7(f+1)=5(f-2) | | -6x-13=x-23 | | x-y=31 | | x^2-6x-4=8 | | (2x+9)+x=90 | | -27.4=p-8.8 | | x+(3*3*3)=3*X-(10*10) | | 0.5(8x-16)=0.666(6x+12) | | h=1+30t-5t^2 | | sqrt(x)-4=2-x | | x^7/5=4 | | 12=-(6-6a)-3(a-6) | | 128=4k+5(6+2k) | | 10y^15+40y^10+25y^8= | | 4(2x+3)=6-(3-2x) | | d=-16t^2-2t+815 | | 40=8/5y | | -19.7=-8.4+x | | 4z+11=3-11 | | D+4(d+6)=11 | | 98-0.54t=80 |